Re-engineering grid-based quorum replication into binary vote assignment on cloud: A scalable approach for strong consistency in cloud databases - Ainul Azila Che Fauzi, Ainul Azila; Noor Ashafiqa, Noor Ashafiqa; Asiah Mat, Asiah; Syerina Azlin Md Nasir, Syerina Azlin; A. Noraziah, Noraziah (The Science and Information (SAI) Organization Limited, 2025)
The growth of cloud computing has heightened the demand for replication strategies that ensure strong consistency, high availability, and low communication cost across distributed infrastructures. Existing systems such as DynamoDB, FoundationDB, and GeoGauss illustrate different design tradeoffs but face limitations in balancing latency, correctness, and resilience under dynamic workloads. This study proposes the Binary Vote Assignment in Cloud (BVAC), a cloud-native replication algorithm re-engineered from the Binary Vote Assignment on Grid Quorum (BVAGQ). BVAC organizes replicas in a logical grid structure and employs binary voting weights with a Commit Coordination (BCC) mechanism to enforce quorumvalidated commits, representing a form of quorum-based replication. This design maintains serializable consistency, minimizes replication conflicts, and reduces low communication cost through fixed-size quorums of three to five replicas. Experimental results demonstrate that BVAC sustains fault tolerance, achieves cloud database replication efficiency, and sustains high data availability via multiple valid quorum paths. By avoiding the heavy coordination cost and infrastructure footprint of current systems, BVAC provides a scalable and cost-efficient replication strategy tailored for modern cloud workloads. The study establishes BVAC as an advancement in distributed data management and a foundation for future adaptive and multi-cloud replication frameworks.